Polarizing film with optical functional layer, and liquid crystal display device

JP2025024040AActive Publication Date: 2025-02-19NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024195800
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-03-06
Filing Date
2024-11-08
Publication Date
2025-02-19
Estimated Expiration
2038-03-05

AI Technical Summary

Benefits of technology

【0017】 本発明の光学機能層付偏光フィルムでは、色素を含有する光学機能層を有する。前記光学機能層は、色素によって、一部の波長の光を吸収することにより、液晶表示装置の全体の色相を調整することができ、広色域化によって鮮やかさを向上させることができる。特に、波長域470~510nmおよび波長域570~610nmのいずれか少なくとも一方に極大吸収波長を有する色素は、RGB以外の波長域(波長域470~510nmおよび/または波長域570~610nm)での色表現に不要な発光を吸収して前記不要な発光を抑えることができ、広色域化に有効である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024040000001_ABST
    Figure 2025024040000001_ABST
Patent Text Reader

Abstract

To provide a polarizing film with an optical functional layer which offers good temporal stability and contains a pigment capable of maintaining a wide color gamut caused thereby.SOLUTION: A polarizing film with an optical functional layer is provided, comprising an optical functional layer A containing a pigment and a polyvinyl alcohol polarizer P arranged such that a distance x therebetween is 45 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing film with an optical functional layer, which has an optical functional layer having a dye and a polarizing film having a polyvinyl alcohol-based polarizer. The polarizing film with an optical functional layer can be used alone or as an optical film laminated with the optical functional layer to form an image display device such as a liquid crystal display device (LCD) or an organic electroluminescence display device. [Background technology]

[0002] In image display devices and the like, it is essential to place polarizing elements on both sides of a liquid crystal cell due to the image formation method, and a polarizing film is generally attached to the liquid crystal cell. When the polarizing film is attached to the liquid crystal cell, an adhesive is generally used. Also, in order to reduce light loss, the polarizing film and the liquid crystal cell are usually bonded together by using an adhesive. In such a case, since there is an advantage that a drying process is not required to fix the polarizing film, an adhesive layer-attached polarizing film that is previously provided as an adhesive layer on one side of the polarizing film is generally used as the adhesive.

[0003] It has also been proposed to add a dye or pigment to the adhesive layer to color it, thereby imparting any hue to the polarizing film and obtaining a high-contrast liquid crystal display (Patent Document 1). In recent years, image display devices have been required to be brighter and more vivid (i.e., a wider color gamut), and organic electroluminescence display devices (OLEDs) have been attracting attention, but a wider color gamut is also required for liquid crystal display devices. For example, as a method for widening the color gamut of liquid crystal display devices, it has been proposed to laminate a polarizing film on one or both sides of the liquid crystal cell via an adhesive layer containing a dye that exhibits a maximum absorption wavelength in a specific wavelength range (560 to 610 nm) (Patent Documents 2 and 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Specification No. 3052812 [Patent Document 2] JP 2011-039093 A [Patent Document 3] JP 2014-092611 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, the dye can be contained in the adhesive layer, and can also be contained in the film layer applied to the optical member. In this way, by containing the dye in a resin layer such as a film layer or an adhesive layer, an optical functional layer containing the dye can be formed. However, since the optical functional layer contains the dye, the dye in the optical functional layer deteriorates over time from the viewpoint of moisture permeability of the resin layer that is the base of the optical functional layer, and the optical functional layer gradually fades. In particular, when the optical functional layer is an adhesive layer containing a dye, the durability of the adhesive layer is insufficient from the viewpoint of moisture permeability, and even the adhesive layer that was initially colored by the dye gradually fades. In this way, when the dye in the optical functional layer (particularly the adhesive layer) deteriorates over time, it is difficult to maintain the wide color gamut by the dye.

[0006] An object of the present invention is to provide an optically functional layer-attached polarizing film having an optically functional layer containing a dye, which has good stability over time and can maintain the wide color gamut provided by the dye. [Means for solving the problem]

[0007] Means of the Invention The present inventors have conducted extensive research to solve the above problems, and as a result have found the following pressure-sensitive adhesive layer-attached polarizing film, thereby completing the present invention.

[0008] That is, the present invention relates to an optically functional layer-attached polarizing film having a polyvinyl alcohol-based polarizer and an optically functional layer containing a dye on at least one side of the polarizing film, the optically functional layer-attached polarizing film being characterized in that the distance between the polyvinyl alcohol-based polarizer and the optically functional layer containing the dye is 45 μm or less. It is preferable that the distance between the polyvinyl alcohol-based polarizer and the optically functional layer is 25 μm or less.

[0009] In the optically functional layer-attached polarizing film, the pressure-sensitive adhesive layer may be directly laminated on the polyvinyl alcohol-based polarizer.

[0010] The optically functional layer-attached polarizing film may have at least one dye-free layer having a thickness of 45 μm or less between the polyvinyl alcohol-based polarizer and the pressure-sensitive adhesive layer.

[0011] In the optically functional layer-attached polarizing film, the polyvinyl alcohol-based polarizer has an oxygen permeability of 1 [cm 3 / (m 2 ·24h·atm) or less is preferable.

[0012] In the optically functional layer-attached polarizing film, the dye can have a maximum absorption wavelength in at least one of the wavelength ranges of 470 to 510 nm and 570 to 610 nm.

[0013] In the optically functional layer-attached polarizing film, the dye can be a tetraazaporphyrin dye.

[0014] The optically functional layer-attached polarizing film preferably contains 0.01 to 5 parts by weight of the dye relative to 100 parts by weight of a base polymer that forms the resin layer of the optically functional layer.

[0015] In the optically functional layer-attached polarizing film, the dye-containing pressure-sensitive adhesive layer preferably has a thickness of 25 μm or less.

[0016] The present invention also relates to an image display device having the above-mentioned optically functional layer-attached polarizing film. Effect of the Invention

[0017] The polarizing film with an optical functional layer of the present invention has an optical functional layer containing a dye. The optical functional layer can adjust the overall hue of the liquid crystal display device by absorbing light of a certain wavelength with the dye, and can improve vividness by widening the color gamut. In particular, a dye having a maximum absorption wavelength in at least one of the wavelength ranges of 470 to 510 nm and 570 to 610 nm can absorb and suppress unnecessary emission in color expression in wavelength ranges other than RGB (wavelength range 470 to 510 nm and / or wavelength range 570 to 610 nm), and is effective in widening the color gamut.

[0018] It was found that the fading of the dye in the optical functional layer containing the dye is caused by oxygen present in the air or in the resin penetrating the optical functional layer and being activated by heat to attack the dye. It is believed that oxygen penetrates from the top, bottom, left and right sides of the pressure-sensitive adhesive layer.

[0019] In the polarizing film with an optical functional layer of the present invention, the optical functional layer containing the dye is applied to a polarizing film using a polyvinyl alcohol-based polarizer. The polyvinyl alcohol-based polarizer has low oxygen permeability and can prevent oxygen from entering the optical functional layer from the upper or lower surface of the optical functional layer containing the dye. The polarizing film with an optical functional layer of the present invention can prevent oxygen from entering the optical functional layer by using a separator with low oxygen permeability on the other surface of the optical functional layer during the period until specific use, and by applying the film to an adherend with low oxygen permeability such as glass during specific use, and can provide an optical functional layer that can suppress fading (decomposition) of the dye and stably maintain a wide color gamut over time.

[0020] In the polarizing film with an optical functional layer of the present invention, the optical functional layer containing the dye and the polyvinyl alcohol polarizer are laminated so that the distance between them is 45 μm or less. By setting the distance to 45 μm or less, it is possible to prevent oxygen from entering from the end of the polarizing film with an optical functional layer, and it is possible to suppress fading (decomposition) of the dye even at the end of the polarizing film with an optical functional layer, and to stably maintain a wide color gamut over time. [Brief description of the drawings]

[0021] [Figure 1] 1 is a cross-sectional view that illustrates an outline of an optically functional layer-attached polarizing film of the present invention. [Diagram 2] 1 is a cross-sectional view illustrating an embodiment of an optically functional layer-attached polarizing film of the present invention. [Diagram 3] 1 is a cross-sectional view illustrating an embodiment of an optically functional layer-attached polarizing film of the present invention. [Figure 4] 1 is a cross-sectional view illustrating an embodiment of an optically functional layer-attached polarizing film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, embodiments of the optically functional layer-attached polarizing film of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the embodiments shown in the drawings.

[0023] As shown in Fig. 1, the polarizing film with an optical functional layer of the present invention has a polyvinyl alcohol-based polarizer P and an optical functional layer A containing a dye. The polyvinyl alcohol-based polarizer P and the optical functional layer A are laminated so that the distance x between them is 45 µm or less. The shorter the distance x, the more oxygen can be prevented from entering from the end. The distance x is preferably 25 µm or less, more preferably 10 µm or less, further preferably 5 µm or less, and further preferably 1 µm or less.

[0024] Fig. 2 shows a case where the polyvinyl alcohol polarizer P and the optical functional layer A are directly laminated (x=0 μm). Fig. 2 illustrates a polarizing film (single-protected polarizing film) having a transparent protective film F on one side (the side where the optical functional layer A is not provided) of the polyvinyl alcohol polarizer P. Fig. 2 also illustrates a case where a substrate S is provided on the optical functional layer A. Examples of the substrate S used until the polarizing film with an optical functional layer is actually used include a separator and a vapor deposition film. Examples of the substrate S used in actual use include glass and a transparent substrate with a vapor deposition layer.

[0025] FIG. 3 illustrates the embodiment of FIG. 2 having a layer B having a thickness of 45 μm or less between the polyvinyl alcohol polarizer P and the optical functional layer A. FIG. 3 illustrates the embodiment of FIG. 2 having a single layer, but the layer B may also be a combination of multiple layers. Examples of the layer B include a pressure-sensitive adhesive layer and a film layer. The thickness of the layer B can be designed according to the characteristics of each layer within a range of 45 μm or less.

[0026] FIG. 4 illustrates the embodiment of FIG. 2 in which the polyvinyl alcohol polarizer P and the optical functional layer A are directly laminated (x=0 μm), and the optical functional layer A further includes a layer C. Although the layer C is illustrated as being a single layer, a plurality of layers may be combined. Examples of the layer C include a pressure-sensitive adhesive layer and a surface treatment layer (such as a hard coat layer, an anti-glare treatment layer, and an anti-reflection layer). The thickness of the layer C can be designed according to the characteristics of each layer within a range of 45 μm or less. The layer C can also be applied in combination with the layer B.

[0027] The polarizing film with an optical functional layer of the present invention comprises a polarizing film having a polyvinyl alcohol-based polarizer and an optical functional layer containing a dye. Each of the members will be described below.

[0028] <Optical functional layer> The optical functional layer of the present invention is not particularly limited as long as it is a resin layer containing a dye. Examples of the resin layer include a film layer, a pressure-sensitive adhesive layer, etc. The optical functional layer can be formed from a composition containing a base polymer and a dye.

[0029] <Dye> The dye contained in the optical functional layer of the present invention can be various dyes. Examples of the dye include various compounds such as tetraazaporphyrin, porphyrin, cyanine, azo, pyrromethene, squarylium, xanthene, oxonol, and squaraine. From the viewpoint of widening the color gamut, the dye is preferably a tetraazaporphyrin dye, a porphyrin dye, a cyanine dye, a squaraine dye, and a squaraine dye, and more preferably a tetraazaporphyrin dye. The dye is specifically disclosed in JP-A-2011-116818. The dye may be used alone or in combination of two or more.

[0030] The dye preferably has a maximum absorption wavelength in at least one of the wavelength ranges of 470 to 510 nm and 570 to 610 nm. A dye having a maximum absorption wavelength in the wavelength range can absorb and suppress unnecessary emission for color expression, and is effective for widening the color range. As a dye having a maximum absorption wavelength in the wavelength range, a tetraazaporphyrin dye can be suitably used. For example, a dye having a maximum absorption wavelength in the wavelength range of 570 to 610 nm includes a tetraazaporphyrin compound (product name: PD-320, PD311) manufactured by Yamamoto Kasei Co., Ltd. and a tetraazaporphyrin compound (product name: FDG-007) manufactured by Yamada Chemical Co., Ltd. The maximum absorption wavelength of the dye was measured using a spectrophotometer (V-570 manufactured by JASCO Corporation).

[0031] The content of the dye in the optical functional layer of the present invention is adjusted depending on the absorption wavelength region and absorption coefficient of the dye and the type of base polymer, but is usually preferably 0.01 to 5 parts by weight, more preferably 0.05 to 3 parts by weight, and even more preferably 0.1 to 1 part by weight, relative to 100 parts by weight of the base polymer. In particular, when a tetraazaporphyrin dye is used, the above range is preferable.

[0032] <Adhesive layer> The optical functional layer of the present invention can be a pressure-sensitive adhesive layer containing a dye, and the pressure-sensitive adhesive layer can be formed from a pressure-sensitive adhesive composition containing a pressure-sensitive adhesive base polymer and a dye. The type of the pressure-sensitive adhesive base polymer is not particularly limited, and can be, for example, various polymers such as rubber-based polymers, (meth)acrylic-based polymers, silicone-based polymers, urethane-based polymers, vinyl alkyl ether-based polymers, polyvinyl alcohol-based polymers, polyvinyl pyrrolidone-based polymers, polyacrylamide-based polymers, and cellulose-based polymers.

[0033] The pressure-sensitive adhesive composition of the present invention contains an adhesive base polymer as a main component. The main component refers to a component that is contained in the largest proportion of the total solid content contained in the pressure-sensitive adhesive composition, for example, a component that occupies more than 50 wt % of the total solid content contained in the pressure-sensitive adhesive composition, and further refers to a component that occupies more than 70 wt %.

[0034] Among these adhesive base polymers, those that are excellent in optical transparency, exhibit appropriate adhesive properties such as wettability, cohesion, and adhesion, and are excellent in weather resistance and heat resistance are preferably used. As a material that exhibits such characteristics, (meth)acrylic polymers are preferably used. Hereinafter, an acrylic adhesive that uses a (meth)acrylic polymer containing alkyl (meth)acrylate as a monomer unit as a base polymer as a material for forming the adhesive layer will be described.

[0035] <(Meth)acrylic polymer> The (meth)acrylic polymer generally contains an alkyl (meth)acrylate as a main component as a monomer unit. Note that the (meth)acrylate refers to an acrylate and / or a methacrylate, and the (meth) in the present invention has the same meaning.

[0036] The alkyl (meth)acrylate constituting the main skeleton of the (meth)acrylic polymer can be exemplified by linear or branched alkyl groups having 1 to 18 carbon atoms. These can be used alone or in combination. The average carbon number of these alkyl groups is preferably 3 to 9.

[0037] From the standpoint of adhesive properties, durability, adjustment of phase difference, adjustment of refractive index, etc., alkyl (meth)acrylates containing an aromatic ring, such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate, can be used.

[0038] In the (meth)acrylic polymer, one or more types of copolymerizable monomers having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group can be introduced by copolymerization in order to improve adhesion and heat resistance. Specific examples of such copolymerizable monomers include hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methylacrylate; (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, and the like. Examples of the monomers include carboxyl group-containing monomers such as acrylates, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamide propanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; and phosphoric acid group-containing monomers such as 2-hydroxyethyl acryloyl phosphate.

[0039] In addition, (N-substituted) amide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; alkylaminoalkyl(meth)acrylate monomers such as aminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and t-butylaminoethyl(meth)acrylate; alkoxyalkyl(meth)acrylate monomers such as methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; N-(meth)acryloyloxymethylene succinimide and N-(meth)acryloyloxymethylene succinimide; Examples of monomers for the purpose of modification include succinimide-based monomers such as acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyoctamethylene succinimide, and N-acryloylmorpholine; maleimide-based monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; and itaconimide-based monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide.

[0040] Further, as the modifying monomer, vinyl monomers such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, N-vinylcaprolactam, etc.; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; acrylic ester monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, silicone (meth)acrylate, and 2-methoxyethyl acrylate, etc., can also be used. Furthermore, isoprene, butadiene, isobutylene, vinyl ether, etc. can be mentioned.

[0041] Further, as copolymerizable monomers other than those mentioned above, there may be mentioned silane-based monomers containing silicon atoms, etc. Examples of the silane-based monomers include 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltriethoxysilane, 10-acryloyloxydecyltriethoxysilane, etc.

[0042] Examples of copolymerizable monomers include tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol. Polyfunctional monomers having two or more unsaturated double bonds such as (meth)acryloyl groups, vinyl groups, etc., such as esters of (meth)acrylic acid and polyhydric alcohols, such as hexa(meth)acrylate and caprolactone-modified dipentaerythritol hexa(meth)acrylate, and polyester (meth)acrylates, epoxy (meth)acrylates, urethane (meth)acrylates, etc., in which two or more unsaturated double bonds such as (meth)acryloyl groups, vinyl groups, etc. are added as functional groups similar to those of the monomer components to the backbone of polyester, epoxy, urethane, etc., can also be used.

[0043] The (meth)acrylic polymer has an alkyl (meth)acrylate as a main component in the weight ratio of all constituent monomers, and the ratio of the copolymerizable monomer in the (meth)acrylic polymer is not particularly limited, but the ratio of the copolymerizable monomer in the weight ratio of all constituent monomers is preferably about 0 to 20%, about 0.1 to 15%, or even about 0.1 to 10%.

[0044] Among these copolymerization monomers, hydroxyl group-containing monomers and carboxyl group-containing monomers are preferably used from the viewpoint of adhesion and durability. Hydroxyl group-containing monomers and carboxyl group-containing monomers can be used in combination. When the pressure-sensitive adhesive composition contains a crosslinking agent, these copolymerization monomers become reaction sites with the crosslinking agent. Hydroxyl group-containing monomers and carboxyl group-containing monomers are highly reactive with intermolecular crosslinking agents, and are preferably used to improve the cohesiveness and heat resistance of the resulting pressure-sensitive adhesive layer. Hydroxyl group-containing monomers are preferred from the viewpoint of reworkability, and carboxyl group-containing monomers are preferred from the viewpoint of achieving both durability and reworkability.

[0045] When the copolymerization monomer contains a hydroxyl group-containing monomer, the content is preferably 0.01 to 15% by weight, more preferably 0.03 to 10% by weight, and further preferably 0.05 to 7% by weight.When the copolymerization monomer contains a carboxyl group-containing monomer, the content is preferably 0.05 to 10% by weight, more preferably 0.1 to 8% by weight, and further preferably 0.2 to 6% by weight.

[0046] The (meth)acrylic polymer of the present invention is usually used with a weight average molecular weight in the range of 500,000 to 3,000,000. In consideration of durability, particularly heat resistance, it is preferable to use a weight average molecular weight of 700,000 to 2,700,000. It is more preferable to use a weight average molecular weight of 800,000 to 2,500,000. If the weight average molecular weight is less than 500,000, it is not preferable in terms of heat resistance. Also, if the weight average molecular weight is more than 3,000,000, it is not preferable because a large amount of dilution solvent is required to adjust the viscosity to be applied, which increases the cost. The weight average molecular weight refers to a value measured by GPC (gel permeation chromatography) and calculated in terms of polystyrene.

[0047] Such a (meth)acrylic polymer can be produced by appropriately selecting a known production method such as solution polymerization, radiation polymerization such as UV polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The obtained (meth)acrylic polymer may be any of a random copolymer, a block copolymer, a graft copolymer, etc.

[0048] In the solution polymerization, for example, ethyl acetate, toluene, etc. are used as a polymerization solvent. In a specific example of the solution polymerization, the reaction is carried out under a stream of an inert gas such as nitrogen, by adding a polymerization initiator, usually at about 50 to 70° C., for about 5 to 30 hours.

[0049] The polymerization initiator, chain transfer agent, emulsifier, etc. used in the radical polymerization are not particularly limited and can be appropriately selected and used. The weight average molecular weight of the (meth)acrylic polymer can be controlled by the amount of the polymerization initiator and chain transfer agent used and the reaction conditions, and the amount of each of these is appropriately adjusted depending on the type of the polymerization initiator and chain transfer agent used.

[0050] Examples of the radical polymerization initiator include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate; di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butyl ... Examples of the initiator include, but are not limited to, peroxide initiators such as butyl peroxydicarbonate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butyl peroxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butyl hydroperoxide, and hydrogen peroxide; and redox initiators combining a peroxide and a reducing agent, such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peroxide and sodium ascorbate.

[0051] The radical polymerization initiators may be used alone or in combination of two or more kinds. The total content is preferably about 0.005 to 1 part by weight, and more preferably about 0.02 to 0.5 parts by weight, per 100 parts by weight of the monomer.

[0052] Examples of the chain transfer agent include lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, 2,3-dimercapto-1-propanol, etc. The chain transfer agent may be used alone or in combination of two or more kinds, but the total content is about 0.1 part by weight or less with respect to 100 parts by weight of the total amount of the monomer components.

[0053] Examples of emulsifiers used in emulsion polymerization include anionic emulsifiers such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, polyoxyethylene alkyl ether ammonium sulfate, and sodium polyoxyethylene alkyl phenyl ether sulfate, and nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyethylene fatty acid ester, and polyoxyethylene-polyoxypropylene block polymer. These emulsifiers may be used alone or in combination of two or more.

[0054] Furthermore, as reactive emulsifiers, emulsifiers having radical polymerizable functional groups such as propenyl groups and allyl ether groups are specifically exemplified by Aqualon HS-10, HS-20, KH-10, BC-05, BC-10, and BC-20 (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and Adeka Reasoap SE10N (manufactured by Asahi Denka Kogyo Co., Ltd.). Reactive emulsifiers are preferred because they are incorporated into the polymer chain after polymerization, improving water resistance. The amount of emulsifier used is 0.3 to 5 parts by weight, and more preferably 0.5 to 1 part by weight, based on 100 parts by weight of the total amount of monomer components, in terms of polymerization stability and mechanical stability.

[0055] <Crosslinking agent> Furthermore, in the present invention, a crosslinking agent can be contained in the adhesive composition forming the adhesive layer having the dye. As the crosslinking agent, an organic crosslinking agent or a polyfunctional metal chelate can be used. As the organic crosslinking agent, an isocyanate crosslinking agent, a peroxide crosslinking agent, an epoxy crosslinking agent, an imine crosslinking agent, etc. can be mentioned. In the polyfunctional metal chelate, a polyvalent metal is covalently bonded or coordinately bonded to an organic compound. As the polyvalent metal atom, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. can be mentioned. As the atom in the organic compound that is covalently bonded or coordinately bonded, an oxygen atom can be mentioned, and as the organic compound, an alkyl ester, an alcohol compound, a carboxylic acid compound, an ether compound, a ketone compound, etc. can be mentioned.

[0056] Examples of compounds related to isocyanate-based crosslinking agents include isocyanate monomers such as tolylene diisocyanate, chlorophenylene diisocyanate, tetramethylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, and hydrogenated diphenylmethane diisocyanate, as well as isocyanate compounds and isocyanurates obtained by adding these isocyanate monomers to trimethylolpropane, biuret-type compounds, and urethane prepolymer-type isocyanates obtained by addition reaction of polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, etc. Particularly preferred are polyisocyanate compounds, and are one selected from the group consisting of hexamethylene diisocyanate, hydrogenated xylylene diisocyanate, and isophorone diisocyanate, or polyisocyanate compounds derived therefrom. Here, the polyisocyanate compound selected from the group consisting of hexamethylene diisocyanate, hydrogenated xylylene diisocyanate, and isophorone diisocyanate or derived therefrom includes hexamethylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, polyol-modified hexamethylene diisocyanate, polyol-modified hydrogenated xylylene diisocyanate, trimer-type hydrogenated xylylene diisocyanate, and polyol-modified isophorone diisocyanate, etc. The polyisocyanate compounds exemplified above are preferred because the reaction with hydroxyl groups proceeds rapidly, particularly with the acid and base contained in the polymer acting as a catalyst, and therefore contributes particularly to the rapidity of crosslinking.

[0057] Any peroxide can be used as long as it generates radical active species upon heating or exposure to light and promotes crosslinking of the base polymer of the pressure-sensitive adhesive composition. Taking into consideration workability and stability, it is preferable to use a peroxide with a 1-minute half-life temperature of 80°C to 160°C, and it is more preferable to use a peroxide with a 1-minute half-life temperature of 90°C to 140°C.

[0058] Examples of the peroxide include di(4-t-butylcyclohexyl) peroxydicarbonate (1-minute half-life temperature: 92.1° C.), di-sec-butyl peroxydicarbonate (1-minute half-life temperature: 92.4° C.), t-butyl peroxyneodecanoate (1-minute half-life temperature: 103.5° C.), t-hexyl peroxypivalate (1-minute half-life temperature: 109.1° C.), t-butyl peroxypivalate (1-minute half-life temperature: 110.3° C.), dilauroyl peroxide (1-minute half-life temperature: 116.4° C.), di-n -octanoyl peroxide (1-minute half-life temperature: 117.4°C), 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (1-minute half-life temperature: 124.3°C), di(4-methylbenzoyl)peroxide (1-minute half-life temperature: 128.2°C), dibenzoyl peroxide (1-minute half-life temperature: 130.0°C), t-butylperoxyisobutyrate (1-minute half-life temperature: 136.1°C), 1,1-di(t-hexylperoxy)cyclohexane (1-minute half-life temperature: 149.2°C), and the like. Among these, di(4-t-butylcyclohexyl) peroxydicarbonate (1-minute half-life temperature: 92.1°C), dilauroyl peroxide (1-minute half-life temperature: 116.4°C), dibenzoyl peroxide (1-minute half-life temperature: 130.0°C), etc. are preferably used because of their excellent crosslinking reaction efficiency.

[0059] The half-life of a peroxide is an index showing the decomposition rate of the peroxide, and refers to the time it takes for the remaining amount of the peroxide to be reduced to half. The decomposition temperature for obtaining the half-life at any time and the half-life time at any temperature are listed in the manufacturer's catalog, for example, NOF Corporation's "Organic Peroxide Catalog 9th Edition (May 2003)."

[0060] The amount of the crosslinking agent used is preferably 20 parts by weight or less, more preferably 0.01 to 20 parts by weight, and even more preferably 0.03 to 10 parts by weight, based on 100 parts by weight of the base polymer such as a (meth)acrylic polymer in the pressure-sensitive adhesive composition. If the amount of the crosslinking agent is more than 20 parts by weight, the moisture resistance is insufficient, and peeling is likely to occur in a reliability test or the like.

[0061] Furthermore, the adhesive composition for forming the adhesive layer having the dye of the present invention may contain a silane coupling agent. By using the silane coupling agent, durability can be improved. Specific examples of the silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acrylic group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.

[0062] The silane coupling agent may be used alone or in combination of two or more kinds, but the total content of the silane coupling agent is preferably 0.001 to 5 parts by weight, more preferably 0.01 to 1 part by weight, even more preferably 0.02 to 1 part by weight, and even more preferably 0.05 to 0.6 parts by weight, based on 100 parts by weight of the base polymer such as the (meth)acrylic polymer, which is an amount that improves durability and maintains an appropriate adhesive force to optical members such as liquid crystal cells.

[0063] Furthermore, in the present invention, the adhesive composition forming the adhesive layer having a dye may contain a polyether-modified silicone. For example, the polyether-modified silicone disclosed in JP-A-2010-275522 may be used.

[0064] Furthermore, in the present invention, the adhesive composition forming the adhesive layer having a dye may contain other known additives, such as colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antiaging agents, antioxidants, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particulates, foil-like materials, etc., which can be appropriately added depending on the application. Also, a redox system may be adopted by adding a reducing agent within a controllable range.

[0065] The adhesive composition is used to form an adhesive layer having a dye. When forming the adhesive layer, it is preferable to adjust the amount of crosslinking agent added and to fully consider the effects of the crosslinking temperature and time.

[0066] The crosslinking temperature and time can be adjusted depending on the crosslinking agent used. The crosslinking temperature is preferably 170° C. or less.

[0067] The crosslinking treatment may be carried out at the same temperature as in the drying step of the pressure-sensitive adhesive layer, or may be carried out in a separate crosslinking treatment step after the drying step.

[0068] The crosslinking treatment time can be set in consideration of productivity and workability, but is usually about 0.2 to 20 minutes, and preferably about 0.5 to 10 minutes.

[0069] The method for forming the adhesive layer having the dye is, for example, a method in which the adhesive composition is applied to a separator that has been subjected to a peeling treatment, the polymerization solvent is dried and removed to form an adhesive layer, and then the adhesive layer is transferred to a polarizing film having a polyvinyl alcohol-based polarizer, or a method in which the adhesive composition is applied to a polarizing film having a polyvinyl alcohol-based polarizer, the polymerization solvent is dried and removed to form an adhesive layer on a polarizing film having a polyvinyl alcohol-based polarizer, etc. In addition, when applying the adhesive, one or more solvents other than the polymerization solvent may be newly added as appropriate.

[0070] A silicone release liner is preferably used as the release-treated separator. In the process of applying the adhesive composition of the present invention onto such a liner and drying it to form a pressure-sensitive adhesive layer, a suitable method may be adopted as a method for drying the pressure-sensitive adhesive depending on the purpose. A method of overheating and drying the coating film is preferably used. The heat drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. By setting the heating temperature within the above range, a pressure-sensitive adhesive having excellent adhesive properties can be obtained.

[0071] The drying time can be appropriately selected from among various drying times, and is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 10 minutes, and particularly preferably 10 seconds to 5 minutes.

[0072] In addition, the pressure-sensitive adhesive layer can be formed on the surface of a polarizing film having a polyvinyl alcohol-based polarizer after forming an anchor layer (for example, about 0.5 to 2 μm thick) or performing various adhesion-facilitating treatments such as corona treatment and plasma treatment. In addition, the surface of the pressure-sensitive adhesive layer may be subjected to adhesion-facilitating treatment.

[0073] The pressure-sensitive adhesive layer can be formed by various methods, specifically, for example, roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, extrusion coating using a die coater, etc.

[0074] The thickness of the pressure-sensitive adhesive layer is not particularly limited and is, for example, about 1 to 100 μm. It is preferably 2 to 50 μm, more preferably 2 to 40 μm, and even more preferably 5 to 35 μm. The thickness of the pressure-sensitive adhesive layer containing the dye is preferably 25 μm or less in order to prevent oxygen from entering from the edge of the pressure-sensitive adhesive layer.

[0075] When the pressure-sensitive adhesive layer is exposed, the pressure-sensitive adhesive layer may be protected with a release-treated sheet (separator) until it is put to practical use.

[0076] <Film layer> In addition, the optical functional layer of the present invention may be a film layer containing a dye, and the film layer may be formed from a composition containing a base polymer for film formation and a dye. Examples of the material of the base polymer forming the film layer include the same materials as those constituting the transparent protective film described below. In particular, cellulose resins such as triacetyl cellulose, polyester resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene-based resins), etc. are preferably used as the material. The film layer may be applied to a polyvinyl alcohol-based polarizer using an appropriate adhesive, pressure-sensitive adhesive, etc.

[0077] Various methods can be adopted for forming the film layer containing the dye. For example, when dissolving the pellets of the resin material in a solvent, the dye is mixed to prepare a composition, and the composition is cast or extruded to produce the film layer. At that time, the film layer can be molded to an appropriate thickness. When preparing the composition, additives can be appropriately mixed.

[0078] The thickness of the film layer is not particularly limited and is the same as that of the pressure-sensitive adhesive layer, for example, about 1 to 100 μm. It is preferably 2 to 50 μm, more preferably 2 to 40 μm, and even more preferably 5 to 35 μm. The separator can also be applied to a film layer containing a dye.

[0079] Examples of materials constituting the separator include plastic films such as polyethylene, polypropylene, polyethylene terephthalate, and polyester film; porous materials such as paper, cloth, and nonwoven fabric; and appropriate thin materials such as nets, foam sheets, metal foils, and laminates thereof. Plastic films are preferably used because of their excellent surface smoothness.

[0080] The plastic film is not particularly limited as long as it is a film that can protect the optical functional layer (particularly, the adhesive layer), and examples include polyvinyl alcohol film, polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, ethylene-vinyl acetate copolymer film, etc.

[0081] The thickness of the separator is usually 5 to 200 μm, preferably about 5 to 100 μm. The separator may be subjected to a release and antifouling treatment using a silicone-based, fluorine-based, long-chain alkyl-based or fatty acid amide-based release agent, silica powder, or the like, as required, or an antistatic treatment such as a coating type, kneading type or deposition type. In particular, by appropriately performing a release treatment such as a silicone treatment, a long-chain alkyl treatment or a fluorine treatment on the surface of the separator, the releasability from the optical functional layer (particularly the pressure-sensitive adhesive layer) can be further improved.

[0082] The release-treated sheet used in the preparation of the pressure-sensitive adhesive layer-attached polarizing film can be used as it is as a separator for the optically functional layer-attached polarizing film, which allows simplification in terms of the process.

[0083] The separator has an oxygen permeability of 1 cm 3 / (m 2 The oxygen permeability is preferably 0.8 [cm 3 / (m 2 ·24h ·atm)] or less is preferable, and 0.6 [cm 3 / (m 2 ·24h ·atm)] or less is preferable, and 0.5 [cm 3 / (m 2 The oxygen permeability is determined depending on the material, thickness, etc. The oxygen permeability of the optical member is specifically measured according to the description in the Examples.

[0084] Preferable examples of the separator that can satisfy the low oxygen permeability requirement include polyvinyl alcohol film, polyethylene terephthalate film, aluminum-deposited film, polyacrylonitrile, ethylene vinyl alcohol, etc. The thickness of the film is preferably 10 to 100 μm, and more preferably 25 to 75 μm.

[0085] <Polarizing film> The polarizing film of the present invention has the polyvinyl alcohol-based polarizer. The polyvinyl alcohol-based polarizer has a low oxygen permeability, and the oxygen permeability is 1 [cm 3 / (m 2 ·24h·atm) or less can be satisfied.

[0086] The polarizing film generally used is a polyvinyl alcohol-based polarizer having a transparent protective film on one or both sides thereof.

[0087] The polyvinyl alcohol polarizer is not particularly limited, and various types can be used. Examples of polarizers include hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, which are uniaxially stretched after adsorbing a dichroic substance such as iodine or a dichroic dye, and polyene-based oriented films such as dehydrated polyvinyl alcohol and dehydrochlorinated polyvinyl chloride. Among these, polarizers made of a polyvinyl alcohol film and a dichroic substance such as iodine are suitable. The thickness of these polarizers is not particularly limited, but is generally about 80 μm or less.

[0088] A polarizer obtained by dyeing a polyvinyl alcohol-based film with iodine and stretching it uniaxially can be prepared, for example, by immersing the polyvinyl alcohol-based film in an aqueous solution of iodine to dye it and stretching it to 3 to 7 times its original length. If necessary, it can also be immersed in an aqueous solution of potassium iodide or the like which may contain boric acid, zinc sulfate, zinc chloride, or the like. Furthermore, if necessary, the polyvinyl alcohol-based film can be immersed in water and washed before dyeing. Washing the polyvinyl alcohol-based film with water can wash off dirt and blocking inhibitors on the surface of the polyvinyl alcohol-based film, and also has the effect of preventing unevenness such as uneven dyeing by swelling the polyvinyl alcohol-based film. Stretching may be performed after dyeing with iodine, or may be stretched while dyeing, or may be dyed with iodine after stretching. Stretching can be performed in an aqueous solution of boric acid, potassium iodide, or the like, or in a water bath.

[0089] As the polarizer, a thin polarizer having a thickness of 10 μm or less can be used. From the viewpoint of thinning, the thickness is preferably 1 to 7 μm. Such a thin polarizer is preferable in that it has less thickness unevenness, excellent visibility, and excellent durability due to less dimensional change, and further, the thickness of the polarizing film can be thinned.

[0090] Representative examples of thin polarizers include thin polarizing films described in JP-A-51-069644, JP-A-2000-338329, WO2010 / 100917, PCT / JP2010 / 001460, or JP-A-2010-269002 and JP-A-2010-263692. These thin polarizing films can be obtained by a manufacturing method including a step of stretching a polyvinyl alcohol resin (hereinafter also referred to as PVA resin) layer and a resin substrate for stretching in a laminated state, and a step of dyeing. With this manufacturing method, even if the PVA resin layer is thin, it can be stretched without problems such as breakage due to stretching because it is supported by the resin substrate for stretching.

[0091] As the thin polarizing film, among the production methods including a step of stretching and a step of dyeing a laminate, those obtained by a production method including a step of stretching in an aqueous boric acid solution as described in WO2010 / 100917, PCT / JP2010 / 001460, or Japanese Patent Application Nos. 2010-269002 and 2010-263692 are preferred, in that they can be stretched at a high ratio and have improved polarization performance. In particular, those obtained by a production method including a step of auxiliary in-air stretching before stretching in an aqueous boric acid solution as described in Japanese Patent Application Nos. 2010-269002 and 2010-263692 are preferred.

[0092] As a material for forming the transparent protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. is used. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene-based resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. A transparent protective film is attached to one side of the polarizer by an adhesive layer, and a thermosetting resin or an ultraviolet-curing resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone-based resin can be used as the transparent protective film on the other side. The transparent protective film may contain one or more suitable additives. Examples of additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, coloring inhibitors, flame retardants, nucleating agents, antistatic agents, pigments, and colorants. The content of the thermoplastic resin in the transparent protective film is preferably 50 to 100% by weight, more preferably 50 to 99% by weight, further preferably 60 to 98% by weight, and particularly preferably 70 to 97% by weight. If the content of the thermoplastic resin in the transparent protective film is 50% by weight or less, the inherent high transparency of the thermoplastic resin may not be fully exhibited.

[0093] The thickness of the transparent protective film is not particularly limited and is, for example, about 10 to 90 μm, preferably 15 to 60 μm, and more preferably 20 to 50 μm. When a transparent protective film is disposed between the polyvinyl alcohol polarizer and the adhesive layer containing the dye, a transparent protective film having a thickness adjusted so that the total thickness including the adhesive layer and the like is 45 μm or less is used.

[0094] A functional layer (surface layer) such as a hard coat layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer or an anti-glare layer may be provided on the surface of the transparent protective film to which the polarizer is not adhered.

[0095] The adhesive used for bonding the polarizer and the transparent protective film is not particularly limited as long as it is optically transparent, and various types of adhesives such as water-based, solvent-based, hot-melt, radical curing, and cationic curing types can be used, but water-based adhesives or radical curing adhesives are preferred. The thickness of the adhesive layer is usually about 0.01 to 3 μm, preferably 0.3 to 2 μm, and more preferably 0.5 to 1.5 μm.

[0096] Examples of the layer having no dye (for example, layer B in the embodiment of FIG. 3) that can be provided between the polyvinyl alcohol polarizer and the adhesive layer having the dye include the anchor layer, a transparent protective film applied to the polarizer, an adhesive layer (for bonding the transparent protective film to the polarizer), an adhesive layer (having no dye), a retardation layer (or retardation film), a light scattering layer, a light emitting layer, an undercoat layer, a liquid crystal layer, and a polarizing layer. The layer B can be used as a single layer, or a plurality of layers can be combined. When a plurality of layers B (for example, layers B1 and B2) are used, a layer in which a plurality of layers B are laminated via an adhesive layer having no dye, such as polarizer P / layer B1 / adhesive layer (having no dye) / layer B2 / adhesive layer A (having a dye), can be used. The thickness of the layer B can be designed according to the characteristics of each layer within a range of 45 μm or less. The layer B is also preferably one having low oxygen permeability.

[0097] <Liquid crystal panel> The optically functional layer-attached polarizing film of the present invention can be suitably used when forming a liquid crystal panel. For example, in the case of a pressure-sensitive adhesive layer-attached polarizing film in which the optically functional layer of the optically functional layer-attached polarizing film of the present invention is an adhesive layer, the adhesive layer-attached polarizing film is attached to at least one surface of a liquid crystal cell via the adhesive layer of the adhesive layer-attached polarizing film to form a liquid crystal panel. The adhesive layer-attached polarizing film of the present invention is suitably used on the viewing side of the liquid crystal cell.

[0098] The liquid crystal cell may be of any type, such as TN type, STN type, π type, VA type, or IPS type, but an IPS mode liquid crystal cell is preferably used for the liquid crystal panel of the present invention.

[0099] In addition to the polarizing film, other optical layers can be used to form a liquid crystal panel. The optical layers are not particularly limited, but one or more optical layers that may be used to form a liquid crystal panel, such as a reflector, a semi-transmitting plate, a retardation plate (including a 1 / 2 or 1 / 4 wavelength plate), a viewing angle compensation film, and a brightness improvement film, can be used on the viewing side and / or the back side of the liquid crystal cell.

[0100] <Liquid crystal display device> The liquid crystal display device is formed by using the above-mentioned liquid crystal panel, and by appropriately assembling components such as a lighting system as necessary, and incorporating a driving circuit. Furthermore, when forming the liquid crystal display device, suitable components such as a diffusion plate, an anti-glare layer, an anti-reflection film, a protective plate, a prism array, a lens array sheet, a light diffusion plate, a backlight, etc. can be arranged in one or more layers at suitable positions. Also, suitable liquid crystal display devices such as those using a backlight or a reflector as a lighting system can be formed. EXAMPLES

[0101] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In each example, parts and percentages are all based on weight. Unless otherwise specified below, the room temperature storage conditions are all 23°C and 65% RH.

[0102] <Measurement of weight average molecular weight of (meth)acrylic polymer> The weight average molecular weight (Mw) of the (meth)acrylic polymer was measured by gel permeation chromatography (GPC). The Mw / Mn ratio was also measured in the same manner. Analytical equipment: Tosoh HLC-8120GPC Column: Tosoh G7000H XL+GMH XL +GMH XL Column size: 7.8mmφ×30cm each, total 90cm Column temperature: 40℃ ·Flow rate: 0.8mL / min ·Injection volume: 100μL Eluent: Tetrahydrofuran Detector: Differential refractometer (RI) Standard sample: polystyrene

[0103] <Oxygen permeability measurement> The oxygen permeability was measured using an oxygen permeability measuring device OX-TRAN manufactured by Mocon under conditions of 23°C and 0% RH in accordance with JIS K 7126-2.

[0104] Example 1 <Preparation of polarizing film> To produce a thin polarizing layer, first, a laminate in which a 9 μm-thick PVA layer was formed on an amorphous PET substrate was subjected to air-assisted stretching at a stretching temperature of 130° C. to produce a stretched laminate, then the stretched laminate was dyed to produce a colored laminate, and the colored laminate was further stretched in boric acid water at a stretching temperature of 65° C. to produce an optical film laminate including a 4 μm-thick PVA layer, in which the PVA molecules of the PVA layer formed on the amorphous PET substrate were highly oriented, and iodine adsorbed by dyeing was highly oriented in one direction as a polyiodine ion complex, forming a high-performance polarizing layer. Furthermore, a polyvinyl alcohol-based adhesive was applied to the surface of the polarizing layer of the optical film laminate (thickness of the formed adhesive layer: 1 μm), and a saponified 40 μm-thick first acrylic resin film (oxygen permeability 5 [cm 3 / (m 2 After laminating the thin polarizer (oxygen permeability less than 0.02 [cm 3 / (m 2 We fabricated a one-sided protected polarizing film using a 100% ...

[0105] <Preparation of (meth)acrylic polymer> A monomer mixture containing 100 parts of butyl acrylate, 0.01 parts of 2-hydroxyethyl acrylate, and 5 parts of acrylic acid was charged into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer, and a stirrer. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts of ethyl acetate for 100 parts of the monomer mixture, and nitrogen gas was introduced to replace the nitrogen gas while gently stirring. The liquid temperature in the flask was kept at about 55°C, and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution (solid concentration 30% by weight) with a weight average molecular weight (Mw) of 1.8 million and Mw / Mn=4.1.

[0106] (Preparation of Pressure-Sensitive Adhesive Composition) For 100 parts of the solid content of the acrylic polymer solution produced above, 0.3 parts of benzoyl peroxide (trade name: Niper BMT, manufactured by Nippon Oil & Fats Co., Ltd.), One part of an isocyanate crosslinking agent (Tosoh Corporation's product name: Coronate L) 0.25 parts of tetraazaporphyrin dye (product name PD-320 manufactured by Yamamoto Chemical Industries, Ltd.: has a maximum absorption wavelength at a wavelength of 595 nm), were mixed to obtain a pressure-sensitive adhesive composition.

[0107] (Preparation of polarizing film with adhesive layer) The adhesive composition was applied uniformly directly onto the polarizer (PVA layer) surface of the thin piece-protected polarizing film using an applicator, and then dried for 2 minutes in an air-circulating thermostatic oven at 155°C to form a 20 μm-thick adhesive layer having a dye on the surface of the polarizer, thereby producing an adhesive layer-attached piece-protected polarizing film.

[0108] Example 2 An adhesive layer-attached piece-protected polarizing film was prepared in the same manner as in Example 1, except that in Example 1, a 20 μm-thick adhesive layer without a dye was laminated on the surface of the polarizer, and then a 20 μm-thick adhesive layer with a dye was formed. In addition, the adhesive layer not containing a dye having a thickness of 20 μm was formed by using the same adhesive composition as that used for forming the above-mentioned adhesive layer containing a dye, except that the dye was not blended in. The adhesive layer was formed by uniformly applying the adhesive composition to the surface of a release substrate (Mitsubishi Plastics, Inc. MRF38CK) of a polyethylene terephthalate film treated with a silicone-based release agent with an applicator, drying for 2 minutes in an air-circulating thermostatic oven at 155° C., and transferring the adhesive layer to the polarizer and laminating it.

[0109] Example 3 In Example 1, a 20 μm-thick adhesive layer containing no dye was formed after laminating two layers (total thickness 40 μm) of the 20 μm-thick adhesive layer containing no dye used in Example 2 on the surface of the polarizer, and the same procedure was followed to prepare an adhesive layer-attached piece-protected polarizing film. The formation of the adhesive layer containing no dye was the same as that described in Example 2.

[0110] Example 4 <Preparation of polarizing film> A saponified second acrylic resin film (oxygen permeability 5 [cm 3 / (m 2 The thin double-protected polarizing film was produced by bonding the two films together with an adhesive (adhesive layer thickness: 1 μm).

[0111] (Preparation of polarizing film with adhesive layer) The adhesive composition used in Example 1 was directly and uniformly applied with an applicator to the back surface (the side opposite the adhesive layer) of the second acrylic resin film of each of the above-mentioned two protective polarizing films, and then dried for 2 minutes in an air-circulating thermostatic oven at 155°C to form an adhesive layer having a thickness of 20 μm and containing a dye on the back surface of the second acrylic resin film, thereby producing an adhesive layer-attached piece-protected polarizing film.

[0112] Comparative Example 1 In Example 1, a 20 μm-thick adhesive layer containing no dye was formed after three layers (total thickness 60 μm) of the 20 μm-thick adhesive layer used in Example 2 were laminated on the surface of the polarizer, and an adhesive layer containing no dye was then formed in the same manner as in Example 1, except that a 20 μm-thick adhesive layer containing no dye was formed. The formation of the adhesive layer containing no dye was similar to that described in Example 2.

[0113] Comparative Example 2 In Example 1, the pressure-sensitive adhesive composition was applied to the polarizer (PVA layer) of the thin piece-protected polarizing film, but a saponified 40 μm-thick acrylic resin film (oxygen permeability 5 [cm 3 / (m 2 An acrylic resin film with a pressure-sensitive adhesive layer was prepared in the same manner as in Example 1, except that the film was formed at a temperature of 100° C. for 24 h atm).

[0114] The following evaluations were carried out on the adhesive layer-attached piece-protected or double-protected polarizing films, and adhesive layer-attached acrylic resin films obtained in the above Examples and Comparative Examples. The evaluation results are shown in Table 1.

[0115] (Evaluation of fading) After cutting the sample into a test piece measuring 50 mm long x 25 mm wide, the front and end states (initial state) were photographed using a scanner (specifically, a Canon PIXUS MX923). Next, the sample was subjected to a durability test in which it was left in a thermostatic chamber at 85°C for 24 hours, after which it was removed and returned to room temperature (23°C), and the front and end states (after 24 hours) of the sample were photographed again using the same scanner. The photographs taken before (initial state) and after (24 hours) the test were binarized, and the presence or absence of color loss at the front and the amount of color loss at the ends were measured using the following method.

[0116] <Color loss on the front> The color loss was evaluated visually based on the binarized photographs taken before and after the test pieces were placed in the durability test. The transmittance before and after the test pieces were placed in the durability test is also shown in Table 1. The transmittance was measured using a spectral transmittance meter with an integrating sphere (Dot-3c from Murakami Color Research Laboratory) with the test pieces at 23°C. ○ There is no difference in color compared to before application. × The color is clearly lighter than before it was added.

[0117] <Discoloration at the edge> The longest distance from the peripheral edge of the test piece toward the center where the color had clearly faded was measured with a ruler, and this was evaluated as the color loss (fading progression distance: mm).

[0118] [Table 1]

[0119] In the examples, there was no color loss in the front and the amount of color loss at the ends was small. The color loss at the ends (fading progression distance: mm) is preferably 3 mm or less, more preferably 2 mm or less, and even more preferably 1 mm or less, and is preferably 0 mm. On the other hand, in Comparative Example 1, since the polyvinyl alcohol polarizer is used, color loss was not observed in the front, but the distance between the polyvinyl alcohol polarizer and the optical functional layer (adhesive layer) may exceed 45 μm, and color loss at the ends (fading progression distance: mm) was observed. In Comparative Example 2, since the polyvinyl alcohol polarizer is not used, color loss was observed both in the front and at the ends. [Explanation of symbols]

[0120] P Polyvinyl alcohol polarizer A Optical function layer F Transparent protective film S Separator B, C Other layers x Distance between the adhesive layer and the polyvinyl alcohol polarizer

Claims

1. A polarizing film with an optical functional layer, comprising a polarizing film having a polyvinyl alcohol-based polarizer and a pressure-sensitive adhesive layer containing a dye and a base polymer on at least one side of the polarizing film, the distance between the polyvinyl alcohol-based polarizer and the pressure-sensitive adhesive layer containing the dye being 25 μm or less, a base polymer of the pressure-sensitive adhesive layer is a (meth)acrylic polymer, an adhesive layer and a transparent protective film are provided between the polarizer and the pressure-sensitive adhesive layer, The total thickness of the transparent protective film and the adhesive layer is 25 μm or less, The adhesive layer bonds the polarizer and the transparent protective film, and the adhesive layer has a thickness of 0.01 to 3 μm.

2. The polyvinyl alcohol polarizer has an oxygen permeability of 1 [cm 3 / (m 2 2. The polarizing film with an optical function layer according to claim 1, wherein the viscosity is less than or equal to 24 h atm.

3. 3. The polarizing film with an optical function layer according to claim 1, wherein the pressure-sensitive adhesive layer containing the dye has a thickness of 25 μm or less.

4. 4. The polarizing film with an optical functional layer according to claim 1, wherein the (meth)acrylic polymer has a weight average molecular weight of 500,000 to 3,000,000.

5. 5. An image display comprising the optically functional layer-attached polarizing film according to claim 1.

Citation Information

Patent Citations

  • Adhesive film, polarizing plate provided with the same and liquid crystal device

    JP2005242010A

  • Liquid crystal display device and optical member set for liquid crystal display device

    JP2011039093A

  • Polarizing plate and liquid crystal display device

    WO2014017541A1

  • Polarizing film with pressure-sensitive adhesive layers on both surfaces, and image display device

    WO2016204154A1

  • Circularly polarizing plate for organic el display device and organic el display device

    JP2014092611A